Evaluation and improvement of agronomic practices. On-farm research - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
On-farm research activities in 1986 continued in the areas of training, network establishment, methodology adaptation, technology development on-farm, and technology adaptation to specific areas. One early result is a better understanding of the variability in the adaptation of the newly adopted var. Gloriabamba in different parts of Cajamarca, Peru. In Ipiales, Colombia, a wide selection of technologies which can be adopted one by one is now available to the farmer. Frijolica LS 3.3, released by the Instituto Colombiano Agropecuario in 1985, is being tested in farmer-managed trials in San Vicente (Antioquia, Colombia). Farmers in the area of Funes (Colombia) have adopted the bush bean line Ancash 66, apparently because of its tolerance to poor soils. Agronomic results between exptl. station and on-farm research are analyzed and compared. Results indicate the need for fertilizer, density, and plant protection practices to be developed and tested from an early stage on-farm. For these practices, station trials, however well conducted, are likely to be misleading. (CIAT)